2017
DOI: 10.1007/s10021-017-0163-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine Root Morphology, Biochemistry and Litter Quality Indices of Fast- and Slow-growing Woody Species in Ethiopian Highland Forest

Abstract: Fine root turnover of trees is a major C input to soil. However, the quality of litter input is influenced by root morphological traits and tissue chemical composition. In this study, fine roots of ten tropical woody species were collected from an Afromontane forest in the northern highlands of Ethiopia. The fine roots were analysed for root morphological traits and tissue chemistry measured as proxy carbon fractionations. Based on stem increment, the 10 species were divided into faster-and slowergrowing speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Abiotic photodegradation caused by the relative exposure of the leaf surface to abiotic factors such as UV light could also promote litter decomposition (Liu et al., 2018). Additionally, we cannot ignore the influence of the morphological characteristics of litter on the decomposition rate (Assefa et al., 2018; Jo et al., 2016). It has been suggested that the decomposition rate of litter would increase with the leaf area index due to an increase in temperature and nutrients as well as water exchange between the litter and soil (Liu et al., 2018; Pietsch et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abiotic photodegradation caused by the relative exposure of the leaf surface to abiotic factors such as UV light could also promote litter decomposition (Liu et al., 2018). Additionally, we cannot ignore the influence of the morphological characteristics of litter on the decomposition rate (Assefa et al., 2018; Jo et al., 2016). It has been suggested that the decomposition rate of litter would increase with the leaf area index due to an increase in temperature and nutrients as well as water exchange between the litter and soil (Liu et al., 2018; Pietsch et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…For the initial litter quality, including C and N concentrations, the C:N ratio, lignin concentrations and lignin:N ratio in leaves and roots could predominantly regulate the litter decomposition process (Bhatnagar et al., 2018; Bradford et al., 2016). Meanwhile, the differences in morphological characteristics between leaves and roots and their resource use strategies can potentially affect decomposition (Assefa et al., 2018; Bradford et al., 2016; Goebel et al., 2011). Essentially, leaves are the main above‐ground litter type, and dead fine roots are the most important below‐ground litter type (McCormack et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Roots (< 2mm) are very sensitive to changes in nutrient cycle and micro-conditions in the soil (e.g temperature, moisture, depth) (Han et al, 2019;Inagaki et al, 2009;Tian, 2002). Therefore, monitoring the amount and temporal changes in fine root dynamics may reflect changes in the ecosystem (Assefa et al, 2018;Chen et al, 2017;Vogt et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…We have collected an extensive dataset consisting of the following: (i) Taxonomic alpha and beta diversity of soil bacteria and fungi for mined, restored, and undisturbed soils by deploying next‐generation/deep sequencing technology; (ii) soil properties (pH, soil organic matter [SOM], total, ammonium and nitrate, total and available phosphorus and potassium, iron, calcium, magnesium, copper, zinc, and manganese) for three soil types, and (iii) assessment of three root morphological traits (specific root length [SRL], root tissue density [RTD], and specific root surface area [SRA] of plants in reforested and reference soils). These traits are strong indicators of fine root biomass, function, and turnover (Assefa et al, 2017), and are crucial determinants of SOM (Hüblová & Frouz, 2021).…”
Section: Introductionmentioning
confidence: 99%